Prognostic Value of Tumor‐Infiltrating Lymphocytes in Sinonasal Mucosal Melanoma. (20th August 2021) - Ledderose, Stephan; Ledderose, Carola; Penkava, Josef; Ledderose, Georg J.
Abstract : Objectives/Hypothesis: Tumor‐infiltrating lymphocytes (TILs) predict better outcome in several types of cancers. However, the prognostic value of TILs in sinonasal mucosal melanoma (SNMM) is uncertain. Here, we investigated whether TILs can be used as a prognostic indicator for survival in SNMM. Study Design: Retrospective cohort study. Methods: Patient history and histologic specimens from 27 patients with primary SNMM were retrospectively analyzed. TIL grade was determined and associations between TILs and AJCC tumor stage, overall survival, and recurrence‐free survival were analyzed. Results: Patients with TILs in the primary tumor classified as brisk or non‐brisk survived significantly longer than patients with SNMMs lacking lymphocyte infiltrates. Brisk TILs were associated with the lower T3 stage and increased recurrence‐free and 5‐year survival. Conclusion: Our results indicate that TIL density is a strong prognostic factor for better survival in SNMM. Prospective studies with larger case numbers are warranted to determine whether TILs should be included in future AJCC staging guidelines. Level of Evidence: 3 Laryngoscope, 132:1334–1339, 2022